Polythiophenes with Cationic Phosphonium Groups as Vectors for Imaging, siRNA Delivery, and Photodynamic Therapy - Laure Lichon; Clément Kotras; Bauyrzhan Myrzakhmetov; Philippe Arnoux; Morgane Daurat; Christophe Nguyen; Denis Durand; Karim Bouchmella; Lamiaa Mohamed Ahmed Ali; Jean-Olivier Durand; Sébastien Richeter; Céline Frochot; et al. (Nanomaterials, 2020)
In this work, we exploit the versatile function of cationic phosphonium-conjugated polythiophenes to develop multifunctional platforms for imaging and combined therapy (siRNA delivery and photodynamic therapy). The photophysical properties (absorption, emission and light-induced generation of singlet oxygen) of these cationic polythiophenes were found to be sensitive to molecular weight. Upon light irradiation, low molecular weight cationic polythiophenes were able to light-sensitize surrounding oxygen into reactive oxygen species (ROS) while the highest were not due to its aggregation in aqueous media. These polymers are also fluorescent, allowing one to visualize their intracellular location through confocal microscopy. The most promising polymers were then used as vectors for siRNA delivery. Due to their cationic and amphipathic features, these polymers were found to effectively self-assemble with siRNA targeting the luciferase gene and deliver it in MDA-MB-231 cancer cells expressing luciferase, leading to 30–50% of the gene-silencing effect. In parallel, the photodynamic therapy (PDT) activity of these cationic polymers was restored after siRNA delivery, demonstrating their potential for combined PDT and gene therapy.